2020
DOI: 10.7554/elife.59704
|View full text |Cite
|
Sign up to set email alerts
|

LRRC8A is essential for hypotonicity-, but not for DAMP-induced NLRP3 inflammasome activation

Abstract: The NLRP3 inflammasome is a multi-molecular protein complex that converts inactive cytokine precursors into active forms of IL-1β and IL-18. The NLRP3 inflammasome is frequently associated with the damaging inflammation of non-communicable disease states and is considered an attractive therapeutic target. However, there is much regarding the mechanism of NLRP3 activation that remains unknown. Chloride efflux is suggested as an important step in NLRP3 activation, but which chloride channels are involved is stil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 48 publications
0
38
0
Order By: Relevance
“…Although this review focuses only on direct inhibition of the NLRP3 inflammasome, there is significant interest in the inhibition of upstream processes, which again may lessen the risk of infection. For example, our research group has recently shown that chloride channels are important regulators of the inflammasome, with novel urea-based compounds showing promising indirect inhibition of the NLRP3 inflammasome [ 60 , 61 ]. What is certain is that it will be a highly competitive race to discover the “First-in-Class” small molecule clinical NLRP3 inhibitor, which may have the potential to treat a range of therapeutic areas where inflammation is a significant component.…”
Section: Discussionmentioning
confidence: 99%
“…Although this review focuses only on direct inhibition of the NLRP3 inflammasome, there is significant interest in the inhibition of upstream processes, which again may lessen the risk of infection. For example, our research group has recently shown that chloride channels are important regulators of the inflammasome, with novel urea-based compounds showing promising indirect inhibition of the NLRP3 inflammasome [ 60 , 61 ]. What is certain is that it will be a highly competitive race to discover the “First-in-Class” small molecule clinical NLRP3 inhibitor, which may have the potential to treat a range of therapeutic areas where inflammation is a significant component.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of chloride efflux in regulation of NLRP3 inflammasome activation has been noted and the involvement of the volume regulated anion channel (VRAC) was reported ( 38 , 39 ). Knockout of LRRC8A, a subunit of VRAC, in macrophages resulted in significant impairment of ASC oligomerization, caspase-1 cleavage, and IL-1β processing induced by hypotonicity, showing the critical role of VRAC in the regulation of NLRP3 inflammasome activation ( 40 ). Chloride intracellular channels (CLICs) have been reported to regulate NLRP3 inflammasome activation ( 41 ).…”
Section: Intracellular Events Regulating Nlrp3 Inflammasome Activatiomentioning
confidence: 99%
“…Volume-regulatory pathways for Cl – are mainly provided by VSOR/VRAC ( Nilius et al, 1997 ; Okada, 1997 ). Molecular evidence for an involvement of LRRC8A in RVD was provided by the inhibitory effect of its gene silencing ( Qiu et al, 2014 ; Formaggio et al, 2019 ) and deletion ( Voss et al, 2014 ; Friard et al, 2017 ; Kang et al, 2018 ; Trothe et al, 2018 ; Green et al, 2020 ). Swelling-activated VSOR/VRAC activity was recently shown to be doubly supported by TRPM7 first through molecular expression of LRRC8A depending on the maintenance of steady-state Ca 2+ influx via this cation channel and second through stabilizing plasmalemmal LRRC8A expression depending on the physical protein-protein interaction with the C -terminal domain of TRPM7 ( Numata et al, 2021 ).…”
Section: Physiological Roles Of Volume-sensitive Outwardly Rectifying Anion Channel/volume-regulated Anion Channel Maxi-anion Channel Andmentioning
confidence: 99%